2014
DOI: 10.1007/s00792-013-0625-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of archaeal diversity in meromictic, hypersaline Ocnei Lake (Transylvanian Basin, Romania)

Abstract: Saline, meromictic lakes with significant depth are usually formed as a result of salt mining activity. Ocnei Lake is one of the largest Transylvanian (Central Romania) neutral, hypersaline lake of man-made origin. We aimed to survey the seasonal dynamics of archaeal diversity in the water column of Ocnei Lake by employing microbiological methods as well as molecular techniques based on the sequence analysis of the 16S rRNA gene. We found that archaeal diversity in the water column increased with depth and sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…The relative abundance of Archaea in the 0.5 (~2%) and 2 m (1.2%) depth assemblages was minor, and could be attributed to the lower salinity levels found at these depths (that is,~70 g l − 1 ). Similar findings were reported in other saline lakes (Yau et al, 2013;Baricz et al, 2014) or shallow ponds (Ghai et al, 2011), and are supported by the fact that most haloarchaeal species lyse at salt concentrations of o100 g l − 1 (Andrei et al, 2012). As the salinity increased over 240 g l − 1 (at 3.5 m depth) the proportion of the Archaea in the communities was higher, ranging between~20% (at 3.5 m depth) and~40% (at 9 m depth), but nonetheless lower than the bacterial one.…”
Section: Vertical Patterns In Prokaryotic Abundancessupporting
confidence: 80%
See 1 more Smart Citation
“…The relative abundance of Archaea in the 0.5 (~2%) and 2 m (1.2%) depth assemblages was minor, and could be attributed to the lower salinity levels found at these depths (that is,~70 g l − 1 ). Similar findings were reported in other saline lakes (Yau et al, 2013;Baricz et al, 2014) or shallow ponds (Ghai et al, 2011), and are supported by the fact that most haloarchaeal species lyse at salt concentrations of o100 g l − 1 (Andrei et al, 2012). As the salinity increased over 240 g l − 1 (at 3.5 m depth) the proportion of the Archaea in the communities was higher, ranging between~20% (at 3.5 m depth) and~40% (at 9 m depth), but nonetheless lower than the bacterial one.…”
Section: Vertical Patterns In Prokaryotic Abundancessupporting
confidence: 80%
“…Even though the bacterial abundance was comparable to that typically described for high-salt environments (Demergasso et al, 2008;Baricz et al, 2014), the fact that they constituted~78% of the monimolimnion community was unanticipated, as previous studies reported the dominance of Archaea at salinities 4300 g l − 1 (Ghai et al, 2011;Baricz et al, 2014). We assume that the increased abundance of Bacteria in the deeper water strata could be achieved by outcompeting Archaea in suboxic hypersaline conditions, as the majority of halophilic archaeal species are aerobic (Andrei et al, 2012).…”
Section: Vertical Patterns In Prokaryotic Abundancessupporting
confidence: 63%
“…Phylogenetically diverse halophilic and highly halotolerant archaea are common in hypersaline systems and include members of the class Halobacteria (Andrei et al ). Extreme halophilic archaea have been isolated from hypersaline lakes in the Transylvanian Basin close to the salt minos of Turda (Baricz et al , ). Novel archaea isolated from commercial salt include Halarchaeum acidophilum (Minegishi et al ) and Natronoarchaeum mannanilyticum (Shimane et al ).…”
Section: Saline and Hypersaline Habitatsmentioning
confidence: 99%
“…Further, we developed a pipeline for accurate phylogenetic assignment of obtained se-quences to the genus level by comparison to a curated database of validly described Halobacteria species using BLASTN (12). Within saline and hypersaline ecosystems, the level of and spatiotemporal fluctuations in salinity obviously play an important role in selection of taxa (34), although the impact of other factors, e.g., pH, temperature, physical characteristics, availability of dissolved O 2 , redox potential, and ionic composition (35), could not be discounted.…”
mentioning
confidence: 99%